Structure-based design generated novel hydroxamic acid based preferential HDAC6 lead inhibitor with on-target cytotoxic activity against primary choroid plexus carcinoma - Shaymaa E. Kassab; Samar Mowafy; Aya M. Alserw; Joustin A. Seliem; Shahenda M. El-Naggar; Nesreen N. Omar; Mohamed M. Awad (Taylor & Francis Group, 2019)
Histone deacetylase 6 (HDAC6) is an attractive target for cancer therapeutic intervention. Selective HDAC6 inhibitors is important to minimise the side effects of pan inhibition. Thus, new class of hydroxamic acid-based derivatives were designed on structural basis to perform preferential activity against HDAC6 targeting solid tumours. Interestingly, 1-benzylbenzimidazole-2-thio-N-hydroxybutanamide 10a showed impressive preference with submicromolar potency against HDAC6 (IC50 = 510 nM). 10a showed cytotoxic activity with interesting profile against CCHE-45 at (IC50 = 112.76 µM) when compared to standard inhibitor Tubacin (IC50 = 20 µM). Western blot analysis of acetylated-α-tubulin verified the HDAC6 inhibiting activity of 10a. Moreover, the insignificant difference in acetylated-α-tubulin induced by 10a and Tubacin implied the on-target cytotoxic activity of 10a. Docking of 10a in the binding site of HDAC6 attributed the activity of 10a to π-π stacking with the amino acids of the hydrophobic channel of HDAC6 and capture of zinc metal in bidentate fashion. The therapeutic usefulness besides the on-target activity may define 10a as an interesting safe-lead inhibitor for future development.